AN EVOLUTIONARY APPROACH TO LITHIUM CELL MODELLING USING MULTI-GENE GENETIC PROGRAMMING - Boma, Chinelo Grace; Konye , Isaac Chidiebere; Amadi, Oluchukwu Emmanuel (Ayden International Journal of Basic and Applied Sciences, 2025)
The effect of some electro-physical parameters on the open circuit cell voltage of a Lithium ion cell composed of LiFePO4 as cathode and Li4Ti5O12 as anode electrodes were investigated. The electrodes were prepared using local material (starch) as carbon source and domestic microwave oven. The electrophysical parameters studied include the current, capacity, speci fic capacity and energy. A mathematical model describing the influences of the aforementioned parameters was then generated using an evolutionary optimization and artificial intelligence technique called the Multi Gene Genetic Programming (MGGP)